Assessment of secondary surgical repair versus salvage endoscopic correction for persistent (recurrent) vesicoureteral reflux in children: protocol for a systematic review and meta-analysis - Ulugbek Nurmatov; Kobiljon Ergashev; Zafar Abdullaev; Kamron Khidoyatov; Askar Soliev; Sarvar Eshankulov; Davronbek Khaltursunov; Akmal Rakhmatullaev; Saidanvar Agzamkhodjaev (BMJ Open)
Introduction Developing a comprehensive understanding of the current estimates for incidence and prevalence of persistent vesicoureteral reflux (VUR) following ureteroneocystostomy or endoscopic correction is crucial. This knowledge will enable us to develop strategies for shared decision-making. Furthermore, a thorough examination of the available evidence will provide an opportunity to formulate evidence-based policies aimed at preventing VUR persistence.Methods and analysis A systematic review and meta-analysis on the success rate and safety of secondary surgical repair versus salvage endoscopic correction for persistent (recurrent) VUR after failed cases in children will be conducted. The following international electronic databases will be searched: MEDLINE, Embase and The Cochrane Library (from inception to February 2025). For unpublished and ongoing studies, international experts in the field of research will be contacted. There will be no language restrictions; where possible, we will translate literature in languages other than English and report any literature we are unable to translate. The methodological quality of interventional studies (the risk of bias) will be independently assessed in individual studies using the Cochrane Risk of Bias tool 2, and observational studies by The Effective Public Health Practice Project critical appraisal tool. The meta-analyses will be performed using Comprehensive Meta-Analysis, V.4. The current protocol adheres to the Preferred Reporting Items for Systematic reviews and Meta-Analyses Protocol 2015 guidelines, thereby upholding the highest methodological standards.Ethics and dissemination Ethical approval is not required. The outcomes of this systematic review will be presented in conference presentations and published in peer-reviewed journals.PROSPERO registration number CRD42024528369.